Finding an Effective Way of Civil Dispute Resolution - Turkanova, Vladyslava (Teisė, 2021)
The main purpose of this article is to analize the substance of the civil dispute and their effective settlement on the basis of an analysis of modern Ukrainian legal doctrine and legislation, as well as the case law of the European Court of Human Rights and national courts and taking into account modern approaches to dispute resolution in sociology and conflict.